1997
DOI: 10.1177/107319119700400407
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Defensive Response Set on the Relationship Between MMPI and Cognitive Tests Among Heart Transplant Candidates

Abstract: Examination of the relationship between self-reported psychological symptoms (e.g., depression and anxiety) and cognitive tests assumes individuals are highly motivated to both openly disclose psychological symptoms and to extend best-effort on cognitive tests. Situations that change this ideal motivational state on either self-report questionnaires or cognitive tests attenuate the validity of this assumption. To illustrate this problem, this study examined the emotional-cognitive correlation in a clinical ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…A number of studies indicate that psychological factors are related to many domains of NP performance, including attention (Putzke et al 1997;Ross, Putnam, Gass, Bailey, & Adams, 2003), memory (Burt, Zembar, & Niederehe, 1995;Putzke et al, 1997;, executive functioning (Gass, Ansley, & Boyette, 1994), and general intelligence (Ackerman & Heggestad, 1997;Wrobel & Wrobel, 1996). Most of these studies have found modest to moderate relationships between psychological disturbance and performance on NP tests and have focused on the assessment of patients with head injury.…”
Section: Psychological Disturbancementioning
confidence: 96%
“…A number of studies indicate that psychological factors are related to many domains of NP performance, including attention (Putzke et al 1997;Ross, Putnam, Gass, Bailey, & Adams, 2003), memory (Burt, Zembar, & Niederehe, 1995;Putzke et al, 1997;, executive functioning (Gass, Ansley, & Boyette, 1994), and general intelligence (Ackerman & Heggestad, 1997;Wrobel & Wrobel, 1996). Most of these studies have found modest to moderate relationships between psychological disturbance and performance on NP tests and have focused on the assessment of patients with head injury.…”
Section: Psychological Disturbancementioning
confidence: 96%
“…Numerous studies have shown these scales to be useful in distinguishing persons feigning various types of psychiatric disorder from true patients and normal controls (Arbisi & Ben-Porath, 1998;Archer, Handel, Greene, Baer, & Elkins, 2001;Bagby et al, 1997;Cramer, 1995;Elhai, Gold, Frueh, & Gold, 2000;Elhai, Gold, Sellers, & Dorfman, 2001;Larrabee, 1998;Lees-Haley, 1991Nicholson et al, 1997;Pensa, Dorfman, Gold, & Schneider, 1996;Strong, Greene, & Schinka, 2000;Tsushima & Tsushima, 2001). The Infrequency minus Correction (FÀK), or Gough's (1950) Dissimulation index, is another measure that has been used in detecting malingering (Cramer, 1995;Elhai et al, 2000;Elhai et al, 2001;Larrabee, 1998;Lees-Haley, 1991;LeesHaley, 1992;Pensa et al, 1996;Smith & Frueh, 1996;Wetzler & Marlowe, 1990) and defensiveness (Putzke, Williams, & Boll, 1998;Putzke et al, 1997).…”
mentioning
confidence: 98%
“…This manuscript is an attempt to discuss issues of a standardized psychosocial assessment of candidates for RHT. We describe the 'Innsbruck Psychological Screening Program for Resonctructive Hand Transplantation (iRT-PSP)', drawing on evidence from previous reported clinical experience and our own experience in the psychosocial assessment of candidates for RHT which includes a generalized assessment of measures of cognitive functioning, affective status, psychosocial adjustment, coping, QoL, and life satisfaction [5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%